2018
DOI: 10.21608/jssae.2018.36530
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Nano-Selenium in Alleviation of Salinity Adverse Effects on Coriander Plants

Abstract: Nanotechnology is the field of science that opens a large scope of novel application in various fields, especially agricultural biotechnology. Selenium (Se) is an essential trace element for humans and animals and appears to be a beneficial element for many plants. There is increasing evidence showing that low selenium (Se) concentrations may build resistance of plants to environmental stresses. For this purpose, a pot experiment was carried out at The Experimental Farm of the Faculty of Agriculture, Mansoura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…BioSeNPs application increased K + level with reduction of Na + level under two concentrations of NaCl (150 and 200 mM) during the early seedling stage, which promotes the regulation of growth by inference to antioxidant metabolism and cellular stress signalling [ 86 ]. It could be concluded that the enhancement in rapeseed growth, total chlorophyll and mineral contents of seedlings exposed to salt conditions with bioSeNPs application may be due to reducing Na + content in leaves, consequently reducing Na + /K + ratio, osmotic adjustment, ionic balance and antioxidant enzyme activities [ 87 ]. NPs elevate the expression of Na + /H + antiport and tonoplast H + -ATPase at the root membranes and shorten the root apoplast barrier, thus limiting Na + translocation to shoot tissues and reducing Na + toxic effects [ 88 , 89 ], hence improving salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…BioSeNPs application increased K + level with reduction of Na + level under two concentrations of NaCl (150 and 200 mM) during the early seedling stage, which promotes the regulation of growth by inference to antioxidant metabolism and cellular stress signalling [ 86 ]. It could be concluded that the enhancement in rapeseed growth, total chlorophyll and mineral contents of seedlings exposed to salt conditions with bioSeNPs application may be due to reducing Na + content in leaves, consequently reducing Na + /K + ratio, osmotic adjustment, ionic balance and antioxidant enzyme activities [ 87 ]. NPs elevate the expression of Na + /H + antiport and tonoplast H + -ATPase at the root membranes and shorten the root apoplast barrier, thus limiting Na + translocation to shoot tissues and reducing Na + toxic effects [ 88 , 89 ], hence improving salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Organic amendments significantly decreased EC and pH of salt-affected soils (Qadir et al 2022). The application of compost and biochar improved the physical conditions of the soil, which increased the leaching ability of soil and thus resulted in a considerable reduction in salts in the root zone 45 . Biochar is claimed to achieve several sustainability goals, including C sequestration, soil health, and plant growth improvements 18 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Reports now concentrate on employing nanoparticles to avoid excessive dosages of selenium while maintaining biological benefits [ 39 ]. Nano-selenium (SeNPs) has many advantages, such as its small size and higher activity, in addition to the ability to use selenium in its zero oxidation state (Se 0 ) [ 40 ]. The aquatic invertebrates, such as gastropods, bivalves, and crustaceans are good model organisms for studying the nanomaterials toxicological effects [ 41 ].…”
Section: Discussionmentioning
confidence: 99%